2011
DOI: 10.4049/jimmunol.0901641
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Continuous Maturation Signaling to Dendritic Cells by RIG-I–Stimulating Cytosolic RNA Synthesis of Sendai Virus

Abstract: Material Supplementary 1.DC1http://www.jimmunol.org/content/suppl/2010/12/27/jimmunol.090164

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…SeV infection was used as an initial stimulus because it induces IFN-␣/␤ by activating RIG-I, although some reports suggest that it may also activate MDA5 (33). SeV also provides a strong RIG-I-dependent DC maturation stimulus (34). As expected, SeV infection stimulated phosphorylation of IRF-3 and a strong IFN-␣/␤ response from the empty vector-transduced MDDC control.…”
Section: Discussionmentioning
confidence: 68%
“…SeV infection was used as an initial stimulus because it induces IFN-␣/␤ by activating RIG-I, although some reports suggest that it may also activate MDA5 (33). SeV also provides a strong RIG-I-dependent DC maturation stimulus (34). As expected, SeV infection stimulated phosphorylation of IRF-3 and a strong IFN-␣/␤ response from the empty vector-transduced MDDC control.…”
Section: Discussionmentioning
confidence: 68%
“…Transduction of DCs with replication-defective lentiviruses reproducibly achieves efficiencies of Ͼ90% and induces little to no IFN-␣/␤ response or other evidence of DC activation (31,35,36). After 72 h, the MDDCs were infected with SeV, known to activate DCs in a RIG-I-dependent manner (37). The expression of eVP35 or mVP35 was verified by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies have found that in murine systems, the dependency of DC on RIG-I for inducing antiviral responses varies by the different DC subtypes, with conventional DCs relying on RLR activation and plasmocytoid DCs possibly operating independently of RLRs [15,39]. In contrast, an in vitro study using human monocyte-derived DCs found that overexpression of a dominant negative RIG-I construct completely abrogated the induction of cytokines induced by a recombinant Sendai virus vector and only partially inhibited expression of DC maturation markers CD86 and HLA-DR [40]. Recent work has shown that RLRs are differentially expressed in specific DC subsets, wherein CD4+ and CD4−/CD8− DCs, the RLRs may function to program antigen presentation and cytokine production [41].…”
Section: Targeted Therapeutic Applications For Rlr Agonistsmentioning
confidence: 99%